(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This exploration delves into the strategic application of Communicative Language Teaching (CLT) within the realm of English for Specific Purposes (ESP). Investigating the efficacy of CLT methodologies in ESP contexts, the article navigates through the integration of communicative approaches to cater to the specialized language needs of learners. This inquiry unfolds as a valuable contribution to the evolving landscape of language pedagogy, offering insights into the harmonious intersection of general communicative strategies and the specific linguistic demands of ESP domains.